Analysis of Achievements, Findings, and Recommendations for Church Independence: a Case Study of the Gpi Elieser Sentani Congregation - Belwawin, Hendrik; Parinusa, Nelino; Labene, Boas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Church as a socio-religious institution has a great responsibility in its mission, including in terms of economic management and the welfare of its members. The independence of the church in field of funds is the key to ensuring the sustainability and strength of the church. This research focuses on the challenges in the financial aspect after the expansion of its previous organization. Despite showing growth in the number of congregations and several achievements, this church still faces obstacles in achieving financial independence and fund management. This study uses a qualitative descriptive method with an Achievement, Findings, and Recommendations (AFR) analysis approach. Data were collected through in-depth interviews with congregation leaders and questionnaires with participants from congregations. The analysis is carried out by identifying the achievements that have been achieved, the findings or obstacles faced, and providing recommendations for the improvement and independence of the church. The results achieved revealed that the GPI Elieser Sentani congregation experienced a quantitative increase in congregation members and service quality. However, the church still faces obstacles such as dependence on people's offerings, limited resources, and cultural and social adaptation challenges that have an impact on physical development, congregational welfare and independence. From these findings, it is recommended that the GPI Elieser Sentani increase the diversification of sources of income by utilizing its assets and looking for external opportunities. In addition, there is a need to increase managerial and leadership capacity, like the development of innovative economic programs to support the welfare of the congregation.